2009
DOI: 10.1111/j.1442-200x.2008.02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Eleven consecutive years of respiratory syncytial virus outbreaks in Croatia

Abstract: The overall prevalence of RSV infection in Croatian children with acute respiratory illness, and its occurrence in various age groups, has remained stable over the past decade. RSV was found to be the most common cause of bronchiolitis occurring throughout childhood (52.7%; 482/913).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
2
13
0
4
Order By: Relevance
“…Our finding that most patients infected with RSV were infants (22/25: 88%) and most of them (19/22: 86%) had either bronchiolitis or pneumonia fits in well with current knowledge that RSV predominantly infects subjects aged 2 yr or younger [8,31,33,34,37,38]. HAdV infections appear to be less age-dependent [35,36,38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that most patients infected with RSV were infants (22/25: 88%) and most of them (19/22: 86%) had either bronchiolitis or pneumonia fits in well with current knowledge that RSV predominantly infects subjects aged 2 yr or younger [8,31,33,34,37,38]. HAdV infections appear to be less age-dependent [35,36,38].…”
Section: Discussionsupporting
confidence: 89%
“…The 29.6% rate of HAdV in our children's oropharyngeal swabs is about twice the reported seasonal incidence for this virus using nasopharyngeal swabs, which varies from 2% to 17.9% [31,[34][35][36][37][38]. Whether our high percent HAdV rate arises from methodological or geographical differences remains to be elucidated.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, a study that investigating the characteristics of RSV outbreaks in Croatia, Mlinarić-Galinović et al 25 showed that RSV infections were most prevalent among infants aged 0-6 months (59.4% of all proven RSV infections). These findings and the results of the present study indicate that HMPV infections occur in somewhat older children than RSV infections.…”
Section: Discussionmentioning
confidence: 92%
“…25 In general, it seems that male infants may develop bronchiolitis more frequently than female infants regardless of the nature of the infecting virus. 25 In addition, a comparative analysis of the clinical presentation of HMPV-and RSV-infected children conducted in another study revealed no significant differences between those 2 groups, although pneumonia tended to be more frequent in HMPV-infected children 11 which can be explained by the observation that HMPV infects older children than does RSV. RSV outbreaks in Croatia occur on a regular, well-investigated, biennial pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological study concerning Zagreb County have shown that RSV-caused bronchiolitis has been registered in 52.7% of children who were hospitalized due to acute respiratory infection (2). The study confirmed biennial cycle of RSV outbreaks (3).…”
Section: Introductionmentioning
confidence: 99%